CONTRIBUTIONS OF KAMPUNG INGGRIS PARE AND ITS IMPLICATIONS FOR UNSKILLED MUSLIM MIGRANT WORKERS - Helfi Helfi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The advantages of becoming Indonesian Muslim migrant workers abroad (known as TKI) are likely under expectation. Most of the workers engage in the informal sector without proper skills. The income generated from them is marked as the second-largest income after the energy sector. Ironically, most of them are regarded as becoming unavailable to access all form of worker rights appropriately. This research is qualitative research that aimed to describe and analyse the problem which relates to the circumstance of the people of Kediri who have the hight interest of working abroad at informal sector mainly, but without proper skills. The establishment of Kampung Inggris (Village for Learning English) located in Pare, the district of Kediri in East Java offers the people of Kediri many business opportunities since many visitors come to spend their money and time to learn English in Kampung Inggris. It is a highly potential circumstance that can be managed to transform a new economic sector behind the existing sectors such as the existing agricultural sector. This research is qualitative in the form of field research which is narrated analytically descriptively. This study attempts to capture directly how inequality occurs in Kediri people who have a strong interest in becoming an informal worker who does not have adequate skills abroad. The development of English villages in Kediri Regency is a promising business space for indigenous people and other communities around Kediri. The presence of academic tourists to study English has become a prospective economic gap. Ranging from regional tours to culinary, from lodging to bicycle sports, from laundry to stationery. A local potential that has gone international to change the agrarian economy towards a skill-based economy with various subsectors that can be developed with various variants in it.Ngaung indahnya jadi Tenaga Kerja Indonesia (TKI) memang tidak semanis yang dirasakan. Terutama Tenaga Kerja Wanita (TKW) yang bergerak di sector informal tanpa skill yang memadai. Mereka dipuji negara karena dianggap penyumbang devisa yang signifikan. Uang yang mengalir ke Indonesia berada pada peringkat ke dua terbesar setelah devisa dari sector migas. Di negara sana, mereka dijajah lahir dan batin, tapi ketika meninggal, mereka “dibiarkan”. Sebuah resiko yang tidak berimbang. Penelitian ini merupakan penelitian kualitatif dalam bentuk penelitian lapangan yang dinarasikan secara deskriptif analitis. Penelitian ini mencoba memotret langsung bagaimana terjadinya ketimpangan dalam masyarakat Kediri yang mempunyai animo yang kuat untuk menjadi TKI/TKW informal yang tidak memiliki skill memadai ke luar negeri. Perkembangan kampung Inggeris di Kabupaten Kediri menjadi ruang usaha yang menjanjikan bagi pribumi dan masyarakat lain di sekitar Kediri. Kehadiran wisatawan akademik untuk belajar bahasa Inggeris menjadi celah ekonomi yang prospektif. Mulai dari wisata daerah hingga kuliner, dari penginapan hingga olah raga sepeda, dari laundry hingga alat-alat tulis. Sebuah potensi lokal yang telah go internasional untuk mengubah ekonomi agraris menuju ekonomi berbasis skill dengan berbagai subsector yang dapat dikembangkan dengan berbagai varian di dalamnya.